2019
DOI: 10.3390/ijerph16183373
|View full text |Cite
|
Sign up to set email alerts
|

A Smartphone App for Improving Mental Health through Connecting with Urban Nature

Abstract: In an increasingly urbanised world where mental health is currently in crisis, interventions to increase human engagement and connection with the natural environment are one of the fastest growing, most widely accessible, and cost-effective ways of improving human wellbeing. This study aimed to provide an evaluation of a smartphone app-based wellbeing intervention. In a randomised controlled trial study design, the app prompted 582 adults, including a subgroup of adults classified by baseline scores on the Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
126
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 94 publications
(131 citation statements)
references
References 60 publications
4
126
0
1
Order By: Relevance
“…This approach has also been used successfully in a smartphone version that prompted urban dwellers to note the good things in nature. This research found that increases in nature connectedness also helped explain clinically significant improvements in mental health (McEwan et al 2019). A content analysis of the sentences written during the good things in nature task showed that the intervention activated several of the pathways to nature connectedness, namely sensory contact, emotions and beauty (Richardson et al 2015).…”
Section: Applying the Pathways -Research Evidencementioning
confidence: 83%
See 2 more Smart Citations
“…This approach has also been used successfully in a smartphone version that prompted urban dwellers to note the good things in nature. This research found that increases in nature connectedness also helped explain clinically significant improvements in mental health (McEwan et al 2019). A content analysis of the sentences written during the good things in nature task showed that the intervention activated several of the pathways to nature connectedness, namely sensory contact, emotions and beauty (Richardson et al 2015).…”
Section: Applying the Pathways -Research Evidencementioning
confidence: 83%
“…Nature Connectedness is measurable using psychometric scales containing carefully constructed sets of items (for available measures see Tam 2013) and several studies suggest it can be increased through carefully designed interventions to prompt engagement with nature (e.g. Richardson and Sheffield 2017;Passmore et al, 2017;McEwan et al 2019). With regard to demographics, population surveys have shown that nature connectedness is significantly higher in women than men, but relatively consistent across all socio-economic groups such as people working in managerial, skilled and manual occupations (Richardson et al 2019).…”
Section: Nature Connectedness: What It Is and Why It Mattersmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now widely accepted that spending time in natural or semi-natural environments (e.g., forests, grasslands, gardens and parks) can result in significant positive mental and physical health benefits [1][2][3]. For example, the Japanese practice of Shinrin-yoku or 'forest bathing' has been shown to enhance innate immunity via lymphocyte cell activity and can reduce diastolic and systolic blood pressure [4,5]; gardening can provide relief from acute stress and improve symptoms of depression [6,7]; and simply spending time in nature can enhance psychological restoration (the ability to recover from stress) and can facilitate healthy child development [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Shmapped was rated by users as highly functional (M=4.38, SD=.53), moderately engaging (M=3.42, SD=.59), and with moderate promise of impacting on behaviour change (M=3.44, SD=.88), according to the Mobile App Rating Scale-MARS [37]. Self-referral to Shmapped was successful, however referral from health professionals was less successful and reasons for this and recommended approaches to future recruitment are discussed [38,39]. Engagement with Shmapped was not optimal during feasibility testing (i.e.…”
Section: Key Recommendationsmentioning
confidence: 99%